Pediatric traumatic brain injury and educational identification: estimating injury severity using data from a TBI screening tool - Holzrichter, Sarah, author; Sample, Pat, advisor; Greene, David, committee member; Daunhauer, Lisa, committee member (Colorado State University. Libraries, 2013)
Traumatic brain injury is a significant source of disability in children and its sequelae can significantly impact a child's academic abilities and school success. Only a small percentage of children who sustain a TBI, however, will receive academic supports specific to TBI, whether through an IEP, 504 plan, or Response to Intervention. The Brain Check Survey (BCS) is a parent-report screening tool designed to be used in educational settings to screen for past incidents that may have caused brain injuries as well as for behaviors and symptoms that may be related to a past TBI and that are impacting a specific student's school performance. In the state of Colorado, having a parent complete the BCS is one of the steps used to determine if a child has a "credible history" of brain injury that is necessary to qualify the child for services. As of yet, however, there are no guidelines given for how to interpret the portion of the BCS that inquires about past incidents that may have caused a brain injury. The purpose of this study was to develop a model for interpreting this portion of the BCS and for roughly estimating the severity of any of the student's past head-related injuries. An Injury-Severity Classification Model (ISCM) was developed and inter-rater reliability tested for its use. Data from completed BCS forms collected in five different Colorado school districts were used for analysis. Additionally, preliminary testing of the model's construct validity was conducted using the resulting severity groups and their presenting behaviors and symptoms as reported on the BCS. High inter-rater reliability was established for the ISCM and its utility was demonstrated for estimating past injury severity among students already identified as having sustained a TBI and receiving services, as well as among students currently receiving no special services. Recommendations are made for revisions of the Injury-Severity Classification Model (ISCM) and for future research.
Keywords: assessment; traumatic brain injury; schools; education; acquired brain injury